Sustained low‐density lipoprotein‐cholesterol <70 mg/dl is associated with improved cardiovascular outcomes in the clinical setting. (21st December 2021) - Sánchez‐Bacaicoa, Carmen; Galán, Javier; Guijarro, Carlos; Rico‐Martín, Sergio; Monreal, Manuel; Calderón‐García, Julián F.; Aguilar‐Cortés, Eduardo; Sánchez Muñoz‐Torrero, Juan F.; ,
Abstract: Background and aims: Clinical trials have shown that intensive low‐density lipoprotein cholesterol (LDL‐C) lowering improves cardiovascular outcomes among patients with atherosclerotic cardiovascular disease (ASCVD), but data are limited in real clinical practice, particularly for patients with ASCVD informing different territories. Methods: FRENA was a prospective registry of consecutive outpatients with coronary, cerebrovascular or peripheral artery disease. We compared the incidence of recurrent events in patients with sustained LDL‐C levels <70 mg/dl compared with those with ≥70 mg/dl. Results: As of December 2018, 1182 patients were eligible for this study. Among them, 172 (14.5%) had mean LDL‐C levels ≤70 mg/dl, and 1010 (85.5%) had <70 mg/dl. Their clinical characteristics at baseline were similar. During 5 years of follow‐up, 252 patients (21%) suffered major adverse cardiovascular events (MACE). The incidence rates of MACE were 3.42 events per 100 patient‐years (95% confidence interval [95% CI] 2.17–5.14) in patients with levels <70 mg/dl and 5.57 (95% CI, 4.87–6.34) in those with ≥70 mg/dl; the rate ratio was 0.61 (95% CI, 0.39–0.92), p  = 0.019. On multivariable analysis, patients with LDL‐C levels <70 mg/dl were at lower risk for MACE (hazard ratio [HR]: 0.61 [95% CI, 0.39–0.93] p  < 0.05). MACE reduction was driven by a decrease in coronary and peripheral events with no significant effect on stroke. Conclusions: Long‐term sustained LDL‐C <70 mg/dl in the clinical practice is associated with reduction in cardiovascular and peripheral vascular events with no apparent effect on stroke.